KEMAMPUAN REPRESENTASI SUBMIKROSKOPIK SISWA PADA KONSEP IKATAN KIMIA - Chusnur Rahmi; Mujakir Mujakir; Pipi Febriani (Lantanida Journal, 2021)
This study is motivated by the difficulty of leaners to understanding the concept of chemical bonding as a whole. Learning that does not represent submicroscopic level causes leaners difficulty to resolving submicroscopic based chemistry questions. This study aims to describe leaner’s ability in represent the concept of chemical bonding at the submicroscopic level. A qualitative descriptive method used in this study. The participants of the study were 30 leaners XI grade of SMA Negeri 1 Meulaboh. The submicroscopic based test instrument was employed in the study to collect the data. The result of study showed that the leaner’s ability of submicroscopic representation about chemical bonding as a whole falls into the category of enough with a percentage of 58.78%.  The average leaners score is 59.32 included in the criteria of sufficient understanding. Generally, leaners were not able to solve the submicroscopic based questions about chemical bonding as expected. The low ability of submicroscopic representation is due to leaners are not used to describing the ions, electrons, and molecular shapes submicroscopically, understanding of chemical bonding concept that are not yet intact, lack of interest and attention of leaners in receiving concept in the learning process.